Benzo(a)pyrene regulated A549 cell migration, invasion and epithelial-mesenchymal transition by up-regulating long non-coding RNA linc00673. (1st March 2020) - Wu, Yongfeng; Niu, Yuequn; Leng, Jing; Xu, Jinming; Chen, Hanwen; Li, Hongyi; Wang, Luming; Hu, Jian; Xia, Dajing; Wu, Yihua
Highlights: This study validated that benzo(a)pyrene promoted migration, invasion and epithelial-mesenchymal transition in the non-small cell lung cancer cell line A549, which is consistent with previous research. Long non-coding RNA linc00673 has been reported to be a robust regulator in multiple neoplasms, of which the up-regulation was proven to be a critical event in the benzo(a)pyrene-induced A549 cell metastasis. The aryl hydrocarbon receptor (AHR) was an essential participator in the benzo(a)pyrene-induced enhancement of linc00673. Benzo(a)pyrene promoted the expression level of linc00673 in an AHR-dependent manner. Abstract: As a major toxicant which is abundant in tobacco smoking, benzo(a)pyrene (BaP) is considered as a strong carcinogen of lung cancer. In spite of the intensive research, the role that BaP plays in lung cancer still lacks a comprehensive and precise understanding. Recently, a long non-coding RNA, linc00673, has emerged as a central player in different kinds of malignancies, including non-small cell lung cancer (NSCLC). In the present study, we found that BaP with the concentration of no more than 8 μM did not affect cell proliferation in the NSCLC cell line A549, while it significantly enhanced A549 cell migration and invasion. Further results revealed that BaP promoted mesenchymal biomarkers expression and inhibited the major epithelial biomarker E-cadherin in a time and dose dependent manner, which indicated epithelial-mesenchymal transition (EMT) was induced by BaP in A549 cells. Through quantitative real-time PCR, we observed that BaP significantly elevated the expression level of linc00673. While after the knockdown of aryl hydrocarbon receptor (AHR), the up-regulating effect of BaP on linc00673 was reversed. Furthermore, silencing linc00673 significantly suppressed the BaP-induced migration, invasion, and EMT in A549 cells. In summary, our study demonstrates that BaP promotes A549 cell migration, invasion and EMT through up-regulating the expression of linc00673 in an AHR-dependent manner.